AXIN2 promotes degradation of AXIN1 through tankyrase in colorectal cancer cells - Schmidt, Olivia; Brückner, Martina; Bernkopf, Dominic (Febs Journal, 2024)
AXIN1 and AXIN2 are homologous proteins that inhibit the Wnt/β-catenin signaling pathway, which is frequently hyperactive in colorectal cancer. Stabilization of AXIN1 and AXIN2 by inhibiting their degradation through tankyrase (TNKS) allows the attenuation of Wnt signaling in cancer, attracting interest for potential targeted therapy. Here, we found that knockout or knockdown of AXIN2 in colorectal cancer cells increased the protein stability of AXIN1. The increase in AXIN1 overcompensated for the loss of AXIN2 with respect to protein levels; however, functionally it did not because loss of AXIN2 activated the pathway. Moreover, AXIN2 was highly essential in the context of TNKS inhibition because TNKS-targeting small-molecule inhibitors completely failed to inhibit Wnt signaling and to stabilize AXIN1 in AXIN2 knockout cells. The increased AXIN1 protein stability and the impaired stabilization by TNKS inhibitors indicated disrupted TNKS-AXIN1 regulation in AXIN2 knockout cells. Concordantly, mechanistic studies revealed that co-expression of AXIN2 recruited TNKS to AXIN1 and stimulated TNKS-mediated degradation of transiently expressed AXIN1 wild-type and AXIN1 mutants with impaired TNKS binding. Taken together, our data suggest that AXIN2 promotes degradation of AXIN1 through TNKS in colorectal cancer cells by directly linking the two proteins, and these findings may be relevant for TNKS inhibition-based colorectal cancer therapies.
CRIS-Team Scopus Importer:2024-07-26
Keywords: AXIN1; AXIN2; colorectal cancer; TNKS; Wnt pathway